Pojmowanie emocji i znaczenie działań muzycznych w ich rozwijaniu u dziecka w młodszym wieku szkolnym - Kłysz-Sokalska, Natalia (Studia Edukacyjne, 2020)
Emotional education in Poland is superficial,accidental and at times intuitive. Lack of emotional education classes and the governments’ low support of teachers have a negative effect on the treatment of emotional education as important in the development of a child in an early school age. Teachers, by trial and error, try to solve problems on the basis of their effect rather than cause, which often lies in the student’s emotions. Separating emotions from “rational” thinking is a pedagogical mistake. An adult’s awareness of the cognitive nature of emotion can affect not only the leveling up of emotional disorders, but also has impact on the child’s overall cognitive development. By using the most natural activities of music and movement, the student develops his emotionality with the verbalization of emotional experience. Awareness of the emotions experiences as well as their correct naming is the key to the success of emotional education for students.